Low-Complexity Slot-Based Bit Loading for Multicarrier Wireless Systems - Iraqi, Y.; Al-Dweik, A.; Kalil, M. (2018 IEEE 87th Vehicular Technology Conference (VTC Spring), 2018)
In this paper, a low-complexity discrete adaptive bit loading algorithm is proposed for multicarrier systems with uniform power allocation operating in fading environments under the discontinuous bit rates assumption. The algorithm objective is to maximize the overall throughput of the system while guaranteeing that the average bit error rate (BER) remains below a prescribed threshold. The algorithm uses a signal-to-noise ratio (SNR) threshold to group adjacent subcarriers into slots where it allocates the same number of bits for all subcarriers within the slot. The grouping mechanism reduces the complexity of the bit-loading process with negligible throughput degradation as compared to optimal and near-optimal algorithms. In particular scenarios, the achieved complexity reduction may exceed 70% with throughput penalty that is less than 1% as compared to other well established bit loading algorithms.